1996
DOI: 10.1007/bf00020481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of altered phosphoenolpyruvate carboxylase activities on transgenic C3 plant Solanum tuberosum

Abstract: Phosphoenolpyruvate carboxylase (PEPC) genes from Corynebacterium glutamicum (cppc), Escherichia coli (eppc) or Flaveria trinervia (fppc) were transferred to Solanum tuberosum. Plant regenerants producing foreign PEPC were identified by Western blot analysis. Maximum PEPC activities measured in eppc and fppc plants grown in the greenhouse were doubled compared to control plants. For cppc a transgenic plant line could be selected which exhibited a fourfold increase in PEPC activity. In the presence of acetyl-Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
49
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 53 publications
3
49
1
Order By: Relevance
“…The role of PEPC in stomatal opening was also confirmed in epidermal strips of C 3 plants using a PEPC inhibitor (Parvathi and Raghavendra, 1997;Asai et al, 2000). At the whole leaf level, the use of antisense and overexpression of PEPC in Solanum tuberosum also suggested that malate accumulation is involved in stomatal function (Gehlen et al, 1996). This showed that rates of stomatal opening increased in plants overexpressing PEPC and decreased in plants with reduced levels of PEPC.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…The role of PEPC in stomatal opening was also confirmed in epidermal strips of C 3 plants using a PEPC inhibitor (Parvathi and Raghavendra, 1997;Asai et al, 2000). At the whole leaf level, the use of antisense and overexpression of PEPC in Solanum tuberosum also suggested that malate accumulation is involved in stomatal function (Gehlen et al, 1996). This showed that rates of stomatal opening increased in plants overexpressing PEPC and decreased in plants with reduced levels of PEPC.…”
mentioning
confidence: 81%
“…This showed that rates of stomatal opening increased in plants overexpressing PEPC and decreased in plants with reduced levels of PEPC. However, low PEPC levels had no effect on steady-state stomatal conductance and overexpression of PEPC had only a marginal effect (Gehlen et al, 1996).…”
mentioning
confidence: 94%
“…In contrast, only a few reports exist on plants with decreased phosphoenolpyruvate carboxylase activity, and studies of knockout mutants have not been carried out to date. In the inhibition studies, transgenic potato plants with reduced phosphoenolpyruvate carboxylase activity (30% of wild-type activity [Rademacher et al, 2002] and 50% to 70% of wild-type activity [Gehlen et al, 1996]) revealed no significant effect on whole plant and tuber growth. However, metabolite analysis showing only little alteration in leaf metabolism suggests an insufficient reduction of phosphoenolpyruvate carboxylase activity to affect metabolism.…”
Section: Effect Of Enzyme Deletion On Seed Storage Metabolismmentioning
confidence: 97%
“…developing seeds and fruits) of C3 plants, phosphoenolpyruvate carboxylase plays an essential role in the anaplerotic replenishment of citrate cycle intermediates by providing precursors for several biosynthetic pathways, including the biosynthesis of amino acids (Chollet et al, 1996). Several groups have attempted to manipulate assimilate partitioning in heterotrophic tissues of C3 plants (Lebouteiller et al, 2007;Radchuk et al, 2007) or to improve CO 2 fixation in autotrophic tissues of C3 plants (Gehlen et al, 1996;Ku et al, 1999) by overexpressing phosphoenolpyruvate carboxylase. In contrast, only a few reports exist on plants with decreased phosphoenolpyruvate carboxylase activity, and studies of knockout mutants have not been carried out to date.…”
Section: Effect Of Enzyme Deletion On Seed Storage Metabolismmentioning
confidence: 99%
“…Thus, as rates of PEP carboxylation are increased, more C0 2 is released than HC03 fixed. In potato, the respiration rate was increased as PEPC activity incresed (Gehlen et al, 1996;Hausler et al, 1999). Similarly, leaves of rice transformants of T3 generation with 20-fold more PEPC activity increased their respiration rate by up to 1.5 fold relative to non-transformed leaves (Agarie et al, 2001).…”
mentioning
confidence: 99%